Study on Identification and Antibiotic Susceptibility Pattern of Microorganisms Responsible for Hospital-Acquired Infection in Patients with Indwelling Medical Devices (Journal of Brahmanbaria Medical College, 2026)
Background: Hospital-acquired infections have a significant impact on public health issues. Hospital admitted patients with indwelling medical devices have a greater chance of developing nosocomial infections. The purpose of the study to determine the antibiotic suceptibility pattern of micro-organism and selection of appropriate drug for treating the cases of common medical device-associated infection. Material and methods: This cross-sectional study was conducted in the Department of Microbiology, BIRDEM General Hospital from September, 2022 to August, 2023. A total of 112 cases of medical device-associated infection were enrolled during the study period. Endotracheal aspirates (50) urine (50) and blood (12) were collected from patients with Ventilator-Associated Pneumonia (VAP) Catheter-Associated Urinary Tract Infection (CAUTI) and Central Line-Associated Bloodstream Infection (CLABSI) respectively. Microorganisms were isolated and identified by culture and biochemical tests. Antibiotic susceptibility test was done using modified Kirby-Bauer disc diffusion method. Results: From a total of 112 samples, nine different types of organisms were isolated including 33 (29.46%) E. coli, 22 (19.64%) Klebsiella, 30 (26.69%) Acinetobacter, 11 (9.82%) Pseudomonas and various others. Microorganisms showed highest resistance against ciprofloxacin while all of them were intermediate sensitive to colistin. Conclusion: A wide range of microorganisms are responsible for medical device-associated infections with their higher rate of antimicrobial resistance. Identification of these microorganisms with their antibiotic susceptibility pattern helps in choosing the correct antibiotic therapy, thus decreasing the improper use of antibiotics.JBRMC, Volume 08 Issue 01 January 2026 ; 3-8